Surveillance for exotic fruit fly of the subfamily Dacinae (Insecta, Diptera, Tephrididae) and a review of the Dacinae established in Sydney, Australia, between 2010 and 2019. Issue 2 (2nd July 2020) - Dominiak, Bernard C.
ABSTRACT: Sydney has a high plant biosecurity risk due to the volume of international freight and postal items. Additionally, a high number of tourists enter Australia through Sydney. In 1995, an array of fruit fly surveillance traps was established to monitor for exotic fruit fly incursions. Here, the number of detections of the fruit fly subfamily Dacinae (Insecta, Diptera, Tephrididae) was reviewed for the period between 2010 and 2019. The results revealed that no exotic fruit flies were detected during this period. However, many established species were detected and species present were placed into international standards. Bactrocera tryoni, B. cacuminatra, Dacus absonifacies, and D. aequalis were classified as established due to a large number of specimens trapped. Sydney was likely to be an area of low pest prevalence for B. neohumeralis in some years and pest free in other years. Low numbers of B. bancrofti, B. brunnea, B. jarvisi, and B. mayi were trapped, and Sydney was likely to be classified free from these species based on international standards. Also, trapping records indicated that Sydney was free from D. newmani however this species was known to occur in inland NSW. Bactrocera bryoniae and B. endiandrae were likely to be incursions that did not establish in most years.